Derating of an Induction Machine under Voltage and Frequency Deviation - Pepliński, M. (Scientific Journal of Gdynia Maritime University, 2018)
One of the most frequently appearing power quality disturbances is voltage deviation. In addition in autonomic power systems, e.g. in ships, frequency deviation often occurs. It causes additional power losses and increase in thermal loads of induction machines. This paper deals with an effect of voltage and frequency deviation on derating.